A SOCIOLINGUISTIC AND LINGUOCULTURAL APPROACH TO GAMBLING GAMES - Sayidov, Shukrullo (International Conference on Linguistics & Translation, 2025)
This article analyzes the linguistic representation of gambling games as reflected in ancient cultures and folklore, as well as their role within socio-cultural and economic contexts. It presents evidence of the economic impact of gambling games throughout different historical periods. Narratives related to gambling games are widely represented in folk legends, especially among the peoples of Asia and North America. The article also highlights the recognition of gambling in Europe and the Caribbean as a source of tourism and national income. Particular attention is given to phraseological units that emerged from the spread of card games and their influence on the relationship between language and culture in society. The concept of culture is interpreted as a social phenomenon based on the principle of "play".